Multisystem inflammation and susceptibility to viral infections in human ZNFX1 deficiency - Vavassori, Stefano; Kottke, Raimund; Staufner, Christian; Hildebrandt, Friedhelm; Reu-Hofer, Simone; García Moll, Solange; Weber, Achim; Kaur, Hundeep; Ehl, Stephan; Hiller, Sebastian; Geha, Raif; Roscioli, Tony; et al. (The journal of allergy and clinical immunology, 2021)
Background - Recognition of viral nucleic acids is one of the primary triggers for a type I interferon-mediated antiviral immune response. Inborn errors of type I interferon immunity can be associated with increased inflammation and/or increased susceptibility to viral infections as a result of dysbalanced interferon production. NFX1-type zinc finger-containing 1 (ZNFX1) is an interferon-stimulated double-stranded RNA sensor that restricts the replication of RNA viruses in mice. The role of ZNFX1 in the human immune response is not known. - Objective - We studied 15 patients from 8 families with an autosomal recessive immunodeficiency characterized by severe infections by both RNA and DNA viruses and virally triggered inflammatory episodes with hemophagocytic lymphohistiocytosis-like disease, early-onset seizures, and renal and lung disease. - Methods - Whole exome sequencing was performed on 13 patients from 8 families. We investigated the transcriptome, posttranscriptional regulation of interferon-stimulated genes (ISGs) and predisposition to viral infections in primary cells from patients and controls stimulated with synthetic double-stranded nucleic acids. - Results - Deleterious homozygous and compound heterozygous ZNFX1 variants were identified in all 13 patients. Stimulation of patient-derived primary cells with synthetic double-stranded nucleic acids was associated with a deregulated pattern of expression of ISGs and alterations in the half-life of the mRNA of ISGs and also associated with poorer clearance of viral infections by monocytes. - Conclusion - ZNFX1 is an important regulator of the response to double-stranded nucleic acids stimuli following viral infections. ZNFX1 deficiency predisposes to severe viral infections and a multisystem inflammatory disease.